Rapid discovery of self-assembling peptides with one-bead one-compound peptide library - Pei-Pei Yang (Nature Portfolio, 2021)
Self-assembling peptides have a range of potential applications but developing self-assembling sequences can be challenging. Here, the authors report on a one-bead one-compound combinatorial library where fluorescence is used to detect the potential for self-assembly and identified candidates are evaluated.